Atasi Candu Judi Online di Kalangan Dewasa Tangerang Selatan - Fadhil Aryadi; Irhamni Rahman (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2026)
The rise of online gambling has become an urgent social issue among South Tangerang adults, with Indonesia occupying the highest position as an online gambling user globally. This qualitative case study aims to explore the factors that cause adult involvement in online gambling, the recovery process of individuals experiencing addiction, and the role of local stakeholders in efforts to overcome it. The findings of the study revealed five main factors, namely the influence of friendships, situational pressure due to aggressive marketing, early winning experiences, misperceptions of winning strategies, and overconfidence in personal abilities. Recovery efforts undertaken by individuals include transformation of mindset, restriction of negative associations, elimination of access to online gambling platforms, increased spiritual engagement, and participation in productive activities. Meanwhile, stakeholders play a role through community education, collaboration with religious and community leaders, public awareness campaigns, and the provision of family counseling. However, this study found that there is no sustainable structured rehabilitation program. Therefore, this study recommends the development of comprehensive social intervention strategies involving professional psychological support and stronger enforcement of regulations to effectively address online gambling addiction.